Visualized Analysis of Research Publications on Physical Activity among Higher Education Students. - Sweileh, Waleed M. (American Journal of Health Education)
Unhealthy lifestyle habits developed during university years could continue into adulthood. To analyze and map worldwide publications on physical activity among university students. A pre-validated search strategy was used to find relevant articles in the Scopus database. The study period represented three decades (1993–2022). The method retrieved 919 articles. More than half of the articles (n = 491; 53.4%) were published between 2019 and 2022. The International Journal of Environmental and Public Health was the most prolific, but articles published in the PLOS ONE journal were the most influential. Research on the impact of physical activity on mental health (n = 236; 25.7%) was the largest research theme, followed by that on body weight (n = 144; 15.7%). Articles on the effect of screen time and mobile phone use on physical activity received the highest number of citations, while those on physical activity during the COVID-19 pandemic received the highest number of citations per year. The current study provided baseline information on the research activity on physical activity among a category of assumingly healthy individuals. Translation to Health Education Practice: University students need to be targeted to increase their engagement in physical activity.